Trimodal Therapy vs. Radical Cystectomy for Muscle-Invasive Bladder Cancer: A Meta-Analysis - Ding, Hui; Fan, Ning; Ning, Zhongyun; Ma, Deyuan (Frontiers in Oncology, 2020)
Background: To compare the difference between trimodal therapy (TMT) and radical cystectomy (RC) in treating muscle-invasive bladder cancer, we performed a meta-analysis for data from the following database. Methods: We searched PubMed, Chinese biomedicine literature database, the Cochrane Library, China National Knowledge Internet databases, Wanfang databases and Google Scholar up to December 2019. The main outcome measures assessed were overall survival(OS), cancer-specific survival(CSS), mortality and charlson comorbidity score(CCS). Two authors independently assessed the study quality and extracted data. All data were analysed using Review Manager(version 5.3). Results: After database retrieval, article selection, data extraction, and quality assessment, nine articles comprising 5721 cases from TMT group and 48262 cases from RC group were included in this study. The data showed that there was no statistical difference between TMT and RC at less than 10 years OS(pooled HR=1.26, 95% CI: 0.92-1.73, Z=1.46, P=0.14), while OS of RC group was higher than that of TMT group at more than 10 years(pooled HR=1.34, 95% CI: 1.18-1.54, Z=4.33, P<0.0001). As for cancer-specific survival, compared with TMT group, the patients in RC group had longer CSS (pooled HR=1.50, 95% CI: 1.29-1.76, Z=5.15, P<0.00001). Compared with RC, TMT is associated with a significant increase in all-cause mortality and bladder-specific cancer mortality(pooled HR=1.30, 95% CI: 1.16-1.46, Z=4.55, P<0.00001; pooled HR=1.32, 95% CI: 1.15-1.51, Z=3.92, P<0.0001). The bladder cancer patients belonging to CCS ‘0’ score prefered RC(pooled RR=0.94, 95% CI: 0.89-0.98, Z=2.79, P=0.005), while CCS ‘2’ score’s patients were prone to TMT(pooled RR=1.40, 95% CI: 1.29-1.53, Z=7.73, P<0.00001). Conclusions: Overall, this meta-analysis suggests that the efficacy of TMT is non-inferior to that of RC at less than 10-year OS, and RC is superior to TMT at more than 10-year OS. TMT may therefore be regarded as a rational treatment option in well-selected patients that are unfit for surgery or are not willing to experience surgery. In future, it also needs more high quality, large samples RCT studies to verify.